Understanding the Motivations, Morale, and Retention of Special Constables: Findings from a National Survey. (28th August 2018) - Callender, Matthew; Cahalin, Kathryn; Cole, Sam J; Hubbard, Luke; Britton, Iain
Abstract: Special Constables have an established history within British policing. The Special Constabulary has represented an under-researched aspect of policing, with motivations to join, morale, factors relating to length of service and reasons for leaving being poorly understood. This article draws upon data from a national survey of Special Constables undertaken across all police forces in England and Wales. The analysis illustrates differences in motivations, dependent on age, and length of service, with younger Special Constables viewing the role as a pathway to future paid employment as a Regular police officer. The results contradict perspectives that attribute attrition from the Special Constabulary primarily to changes in personal circumstances for Specials, demonstrating how such changes are less important than satisfaction with the experience of being a Special Constable. The article concludes by identifying the significance of the findings for future policy and practice in respect of the Special Constabulary.